Increasing Productivity of USEP KM Casting Chips and Peyek through Technology and Product Packaging Standard Assistance in Nangsri Kidul Village, Semanu, Gunung Kidul, Yogyakarta - Iswanto Suwarno; Robbi Rahim; Mohammad Aljanabi; Omar Tanane; Erwin L. Rimban; Manvender Kaur Sarjit Singh (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2022)
Nangsri Kidul Village is one of the villages in Semanu District, Gunung Kidul Regency. The majority of people in Nangsri Kidul Village work as farmers. Apart from farmers, there are also people who open businesses such as USEP KM Cassava Chips and USEP KM Peyek. However, in Nangsri Kidul Village there are problems faced by the community, namely production technology that is still simple and packaging is still simple. In the USEP KM, the financial administration aspect is not well organized, the product packaging is simple, so it is less attractive and the product is not well protected, and the production technology is still manual, not using a dryer. Therefore, it is necessary to carry out counseling, training, and knowledge of product packaging standards for USEP KM Cassava Chips and USEP KM Projects and the provision of production and packaging equipment. The targets to be achieved are: i) Understanding of product packaging standards; ii) Using modern production technology. This target is achieved through: i) Dissemination and provision of standard product packaging samples; ii) Technological training and making cassava chip dryers and chips. The results of the community service were i) USEP KM was given directions and training on how to pack the product properly and made a product brand label so that the product is known by consumers and the product is not easily damaged; ii) USEP KM was briefed on a more modern technology and developed an automatic dryer to reduce the oil in cassava chips and dents.